1991
DOI: 10.1161/01.res.68.6.1660
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol acutely and reversibly suppresses excitation-contraction coupling in cardiac myocytes.

Abstract: We used adult rat cardiac myocytes to examine the acute effects of 0.1-5.0% (vol/vol)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
64
0
3

Year Published

1993
1993
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(72 citation statements)
references
References 32 publications
(1 reference statement)
5
64
0
3
Order By: Relevance
“…The hallmarks of alcoholic cardiomyopathy are altered cardiac contractile function and impaired intracellular Ca 2ϩ mobilization such as decreased SR Ca 2ϩ function, which may underlie the altered cardiac mechanics (2,3,8,24,29,30). It is postulated that inhibition by ethanol of Ca 2ϩ regulatory proteins such as Ca 2ϩ pumps and channels may play a role in the decreased cytosolic Ca 2ϩ concentration.…”
Section: Discussionmentioning
confidence: 99%
“…The hallmarks of alcoholic cardiomyopathy are altered cardiac contractile function and impaired intracellular Ca 2ϩ mobilization such as decreased SR Ca 2ϩ function, which may underlie the altered cardiac mechanics (2,3,8,24,29,30). It is postulated that inhibition by ethanol of Ca 2ϩ regulatory proteins such as Ca 2ϩ pumps and channels may play a role in the decreased cytosolic Ca 2ϩ concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Rat cardiomyocytes exposed to alcohol have a dose dependant depression in contractility due, at least in part, to a depletion of sarcoplasmic calcium (59). Studies in mice and human tissue have shown that alcohol causes direct myocardial ultrastructural damage, including edema of sarcoplasmic reticulum, fragmentation of contractile elements, expansion of intercalated disc, and fatty deposits (60,61).…”
Section: Animal Models Relating To Alcohol Induced Arrhythmiasmentioning
confidence: 99%
“…In addition, heavy drinking may cause myocyte dysfunction (through abnormalities in calcium homeostasis) and elevated levels of norepinephrine [10,11]. Increasing doses of ethanol have been associated with a negative inotropic effect on myocytes in animal experiments [12]. In humans, acute ethanol ingestion may also lead to depressed myocardial contractility [13].…”
Section: Heavy Alcohol Consumption and Risk Of Hfmentioning
confidence: 99%